The effect of mindfulness meditation training on biological acute stress responses in generalized anxiety disorder. (April 2018) - Hoge, Elizabeth A.; Bui, Eric; Palitz, Sophie A.; Schwarz, Noah R.; Owens, Maryann E.; Johnston, Jennifer M.; Pollack, Mark H.; Simon, Naomi M.
Abstract: Mindfulness-Based interventions have increased in popularity in psychiatry, but the impact of these treatments on disorder-relevant biomarkers would greatly enhance efficacy and mechanistic evidence. If Generalized Anxiety Disorder (GAD) is successfully treated, relevant biomarkers should change, supporting the impact of treatment and suggesting improved resilience to stress. Seventy adults with GAD were randomized to receive either Mindfulness-Based Stress Reduction (MBSR) or an attention control class; before and after, they underwent the Trier Social Stress Test (TSST). Area-Under-the-Curve (AUC) concentrations were calculated for adrenocorticotropic hormone (ACTH) and pro-inflammatory cytokines. MBSR participants had a significantly greater reduction in ACTH AUC compared to control participants. Similarly, the MBSR group had a greater reduction in inflammatory cytokines' AUC concentrations. We found larger reductions in stress markers for patients with GAD in the MBSR class compared to control; this provides the first combined hormonal and immunological evidence that MBSR may enhance resilience to stress. Highlights: Individuals with Generalized Anxiety Disorder in the mindfulness group had a greater drop in stress-related ACTH hormone. Individuals in the mindfulness group also had a greater drop in pro-imflammatory cytokines during the stress task. Findings suggest that mindfulness meditation training may have helped participants cope better with subsequent stress.